CRITICAL STUDY OF OPTIMIZATION OF ISLAMIC CORPORATE GOVERNANCE IMPLEMENTATION TO ACHIEVE COMPANY PERFORMANCE - Pahlevi, Reza Widhar (Indonesian Journal of Accounting and Governance, 2019)
Guidelines for Good Corporate Governance an Islamic perspective have a broader context, do not separate roles and responsibilities in all stakeholders actions under the auspices of Islamic sharia law. There are differences in concepts and perspectives between western perspective (Anglo Saxon and European) Good Corporate Governanceand Islamic perspectives. The difference in the very basic point of view that Good Corporate Governance is the Islamic perspective comes from tawhid, shari'ah, and the concept of shura. Islamic Good Corporate Governance guidelines focus on the role of stakeholders related to the company. The development of science that occurs in the perspective of Good Corporate Governance begins on the basis of agency theory which states that there is a separation between ownership and management that has the potential to cause agency problems, ways to overcome agency problems through the implementation of Good Corporate Governance. Implementation of guidelines for Good Corporate Governance is an obligation for the company. This is more aimed at the existence of responsibility to the public (public accountability) relating to the company's operational activities and it is expected that the company can comply with the provisions outlined in a positive law. In addition, this is related to the level of compliance of sharia with sharia principles as described in the Qur'an, Hadith, and Ijma 'of the Ulama. Research related to Good Corporate Governance in the Islamic perspective with the achievement of company performance is expected to provide an overview of the Good Corporate Governance framework that recognizes the rights of stakeholders as determined by law and encourages active cooperation between companies and stakeholders to create employee welfare, performance, and corporate sustainability.